Numerical Simulation of Carbon Nanotubes/GaAs Hybrid PV Devices with AMPS-1D - Georgi Xosrovashvili; Nima E. Gorji (International Journal of Photoenergy)
The performance and characteristics of a hybrid heterojunction single-walled carbon nanotube and GaAs solar cell are modelled and numerically simulated using AMPS-1D device simulation tool. The device physics and performance with different junction parameters are analysed. The results suggest that the open-circuit voltage changes very slightly by changing the electron affinity, acceptor and donor density while the other electrical parameters reach an optimum value. Increasing the concentration of a discrete defect density in the absorber layer decreases the electrical parameters. The current-voltage characteristics, quantum efficiency, band gap, and thickness variation of the photovoltaic response will be quantitatively considered.